Advanced construction mathematics - Virdi, Surinder Singh (Abingdon, Oxon : Routledge, 2019)
"Advanced Construction Mathematics covers the range of topics that a student must learn in order to achieve success in Level 3 and 4 mathematics for the Pearson BTEC National and BTEC HNC/HND in Construction, Built Environment, and Civil Engineering. Packed with easy to follow examples, the chapters cover algebra (equations, transposition and evaluation of formulae), differentiation, integration, statistics and numerous other core concepts and their application in the construction/civil engineering field. The book simplifies technical processes before applying mathematical techniques to solve practical problems which gradually build in complexity. Each chapter contains self-test exercises and answers and numerous illustrations to simplify the essential maths required at level 3 and 4. The book is also a useful recap or primer for students on BSc or non-cognate MSc Construction and Civil Engineering degrees"--
10.4 Differentiation of function of a function10.5 The chain rule by recognition; 10.6 Differentiation of exponential and logarithm functions; 10.7 Differentiation of a product; 10.8 Differentiation of a quotient; 10.9 Numerical values of differential coefficients; Exercise 10.1; Exercise 10.2; Exercise 10.3; Exercise 10.4; Answers -- Exercise 10.1; Answers -- Exercise 10.2; Answers -- Exercise 10.3; Answers -- Exercise 10.4; Chapter 11: Applications of differentiation; 11.1 Application in structural mechanics; 11.2 Second derivatives; 11.3 Velocity and acceleration; 11.4 Maximum and minimum
OCLC-licensed vendor bibliographic record.
Keywords: Building -- Mathematics; Civil engineering -- Mathematics; TECHNOLOGY & ENGINEERING / Civil / General; TECHNOLOGY / Construction / General; MATHEMATICS / Arithmetic; MATHEMATICS / Geometry / General